Granulometric analyses of basin-wise DEMs: a comparative study - Tay, L. T.; Sagar, B. S. Daya; Chuah, H. T. (TAYLOR & FRANCIS LTD, 2007)
Digital elevation models (DEMs) are very useful for terrain characterization. We apply a morphological approach to characterize 14 sub-basins decomposed from interferometrically generated DEMs of Cameron Highlands and Petaling regions of Peninsular Malaysia. Physiographically, these two regions possess a distinct geomorphologic set-up as they belong to region with higher and lower altitudes, respectively. Fourteen sub-basins are extracted from the DEMs, and pattern spectra by opening and closing of these sub-basins relative to flat discrete binary patterns (square, octagon and rhombus) are computed. Pattern spectra are used to compute probability size distribution functions of both protrusions and intrusions that are conspicuous in topography, based on which shape-size complexity measures of these sub-basins are estimated by means of average roughness and size. Furthermore, fractal dimensions of channel networks derived from these 14 basins are computed by applying the box-counting method. Comparisons between shape-size complexity measures and fractal dimension are carried out.